Assessing the output and productivity of manufacturing sector to the export in Malaysia - Martin, Tulasi; Nallaluthan, Kesavan; Yankteshery, Vijiyan (Nilai Field Consultancy and Training, 2021)
Objective: Malaysia is a developing country that has succeeded in achieving an impressive growth rate of industrial output with a sustainable export policy in the last thirty years. This study mainly focuses on the role of the manufacturing sector in exports in Malaysia. Specifically, this study has objectives of analyzing the factor of the manufacturing sector which is represented by the level of output and productivity, respectively that influence export of Malaysia and relationship between the manufacturing sector and exports in Malaysia. Improvement in the manufacturing sector in Malaysia can be achieved through the growth and strengthening of labor productivity. Research Design & Methods: Regression and correlation methods were used to achieve the study objectives. Secondary data used to estimate empirical models in this study were obtained from statistical publications of the World Bank and Asian Development Bank (ADB). The data covered a period of 1981-2016. The use of simple regression and correlations models was able to test hypotheses that relate to the roles of the manufacturing sector and exports as well as the relationship between the manufacturing sector and exports. Findings: The study findings used regression analysis indicated that there were positive and significant influences of the output and productivity of the manufacturing sector on exports in Malaysia. The findings used correlation analysis indicated that there was a positive and significant relationship between the level of output and productivity that contributes to exports in Malaysia. Implications & Recommendations: This study concludes that Malaysia's exports may increase while the manufacturing sector progresses. Hence, the implication is the need to take restructuring measures in the manufacturing sector to increase productivity growth. Contribution & Value Added: The government has to identify the weaknesses that exist in the manufacturing sector and export activities. This effort will help contribute to increased exports in Malaysia.